Extraction of Color Information and Visualization of Color Differences between Digital Images through Pixel-by-Pixel Color-Difference Mapping - Woo Sik Yoo; Kitaek Kang; Jung Gon Kim; Yeongsik Yoo (Heritage, 2022)
A novel method of extracting color information on a pixel-by-pixel basis or by the average of the regions of interest (ROIs) from digital images is proposed and demonstrated using newly developed and customized image-processing/analysis software (PicMan). For quantitative and statistical analyses of color, the newly developed software can be used for digital archive or digital forensic applications in various fields. The color differences between unrelated, similar, or identical scenes and or objects were quantified in various formats of desired color spaces such as RGB, HSV, XYZ, CIE L*a*b*, Munsell color, and hexadecimal color values. The color differences were visualized as images of pixel-by-pixel mapping of the ΔL*, Δa*, Δb*, ΔERGB, ΔEHSV, and ΔE*L*a*b* values and block comparison images of desired block sizes. Various color analyses and color-difference mapping examples using an aged and damaged oil painting before and after restoration were introduced. The effects of the image file format differences between PNG and JPG on color distortion are demonstrated by statistics and pixel-by-pixel color-difference mapping. A portrait of Chuk-ki Yoo (兪拓基, 1691–1767) on silk from the 18th century from Korea was used for further color analysis for whole and selected areas. A collector’s ownership stamp of Chuk-ki Yoo stamped in red ink on the text areas in one of his book collections was extracted using the image-processing software and superimposed on the original image as a visualization enhancement example. Image analysis, processing, modification, enhancement, and highlighting, as well as statistical color analysis of digital images in most formats, can conveniently and efficiently be performed using one piece of dedicated software (PicMan). The pixel-by-pixel color information extraction and color comparison technique can be very effective for a variety of applications in art and cultural heritage objects.